Bitter and sweet - McKnight, Rhonda (Thomas Nelson, 2024)
"Two sisters at a crossroad in life find the answers to their problems in the lessons from the past... Mariah never pretended her marriage was perfect but that didn't mean she ever suspected her husband of ten years would not only ask for a divorce but steal the business she built for them. Defeated and depressed, she's not sure how to bounce back from the manipulative betrayal. Sabrina has been self-destructing for years, maybe since she was born, but certainly since the death of her long-time boyfriend. Barely scraping by and living in her van, she's struggling to figure out what's next for her, when all she's ever wanted to do is bake cakes like her mother did. When Mariah and Sabrina's grandmother sends them a cryptic text message summoning them to Georgetown, South Carolina, both assume their ailing grandfather's health has declined. Instead, the estranged sisters are faced with their grandmother's undeniable request--save the family restaurant. Through letters written by their great-great-grandmother, Tabitha, Mariah and Sabrina learn a heartbreaking yet powerful story of struggle and survival. As the whole truth about Tabitha's complicated past unfolds, the sisters are inspired by her ability to forge her own way in Charleston, a beautiful and prosperous city that was also rife with oppression under Jim Crow. With the lessons in their family's past guiding them, both sisters have a chance at a different life--if they can find a way to bridge the gap that tragedy and unhealed trauma forced between them. Told in a dual timeline that alternates between the 1920s and present-day Charleston, SC, Bitter and Sweet is an emotional story about love, one family's perseverance, and the bonds of family and heritage." -- back cover.